Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Aplikasi Sistem Informasi Pemerintahan Daerah Dan Kompensasi Terhadap Kinerja Aparatur Badan Keuangan Kota Bukittinggi - Rahmadani, Putri; Khairul, Khairul (CV. ITTC INDONESIA, 2024)
This research aims to investigate the influence of human resource competence, implementation of regional government information system applications and compensation which can improve employee performance. The compensation used in this research is financial compensation. This research uses variance-based structural equations, smart PLS is used to solve variance-based SEM problems. The respondents in this research were 80 employees of the Financial Agency in Bukittinggi City. The results of his research found that human resource competence has a positive and significant influence on performance. Implementation of the Regional Government Information System application has a positive but not significant influence on performance. Compensation has a positive and significant influence on performance. The implementation of SIPD has a positive and significant effect on Human Resource Competency. The application of SIPD to performance through human resource competency is significant.